Обняться, чтобы уцелеть: роман / Олег Рой - Рой Олег (Капризы и странности судьбы, 2019)
Экземпляры: ф.17 (20190422) / Инвентарный номер: 59532 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44